Fire history and weather interact to determine extent and synchrony of mast-seeding in rhizomatous scrub oaks of Florida. (6th December 2021) - Pesendorfer, Mario B.; Bowman, Reed; Gratzer, Georg; Pruett, Shane; Tringali, Angela; Fitzpatrick, John W.
Abstract : In disturbance-prone ecosystems, fitness consequences of plant reproductive strategies are often determined by the relative timing of seed production and disturbance events, but the role of disturbances as proximate drivers of seed production has been overlooked. We use long-term data on seed production in Quercus chapmanii, Q. geminata and Q. inopina, rhizomatous oaks found in south central Florida's oak scrub, to investigate the role of fire history and its interaction with weather in shaping acorn production and its synchrony . Acorn production increased with the time since last fire, combined with additive or interactive effects of spring precipitation (+) or drought (–). Furthermore, multiple matrix regression models revealed that ramet pairs with shared fire history were more synchronous in seed production than ones that burned in different years. Long-term trends suggest that increasingly drier spring weather, in interaction with fire frequency, may drive a decline of seed production. Such declines could affect the community of acorn-reliant vertebrates in the Florida scrub, including endangered Florida scrub-jays ( Aphelocoma coerulescens ). These results illustrate that fire can function as a proximate driver of seed production in mast-seeding species, highlighting the increasingly recognized importance of interactions among reproductive strategies and disturbance regimes in structuring plant populations and communities. This article is part of the theme issue 'The ecology and evolution of synchronized seed production in plants'.